Digital Television Regulation and its Impact on Indonesia towards Society 5.0 - Arsyad Nurizar (Universitas Muhammadiyah Yogyakarta, 2020)
The Indonesian government plans to replace all analog television broadcasts with digital television broadcasts. Through digital broadcasting, the public can enjoy television shows with better picture quality and many new services available. The government has actually made regulations relating to digital broadcasting, but the regulations seem to lack a positive response from the public and have been repeatedly sued in court. Until now, the legal basis for the implementation of digital broadcasting in Indonesia is still waiting for the inclusion of the term digitization in regulation at the legal level. The switch to digital broadcasting has left Indonesia unable to enjoy a digital dividend that can be used to provide faster and more extensive broadband internet. This information is important as a form of preparation for entering the era of society 5.0, where access to the internet has an important role to play in the development of science and technological innovation. This study used descriptive qualitative methods to give describe about the urgency of digital broadcasting regulation in Indonesia and its impact on Indonesia related to the preparation of welcoming the era of society 5.0, where technology will get closer to people's lives to solve various social problems.